Refining Estimates of Greenhouse Gas Emissions From Salt Marsh “Blue Carbon” Erosion and Decomposition - McTigue, Nathan D.; Walker, Quentin A.; Currin, Carolyn A. (Frontiers in Marine Science, 2021)
Coastal wetlands have sediments that contain organic matter preserved against decomposition for timespans that can range up to millennia. This “blue carbon” in wetland sediments has been proposed as a sink for atmospheric carbon dioxide and a potential source of greenhouse gases if coastal habitats are lost. A missing gap in the role of coastal habitats in the global carbon cycle is elucidating the fate of wetland sediment carbon following disturbance events, such as erosion, that can liberate organic matter to an oxygenated environment where decomposition can more readily occur. Here, we track the fate of previously stored salt marsh sediment by measuring the production of carbon dioxide (CO2) and methane (CH4) during an oxygenated incubation. Sediments from two depth horizons (5–10 cm and 20–25 cm) were incubated at two temperatures (20 and 30°C) for 161 days. Q10 of the decomposition process over the entire course of the experiment was 2.0 ± 0.1 and 2.2 ± 0.2 for shallow and deep horizons, respectively. Activation energy for the decomposition reaction (49.7 kJ ⋅ mol–1 and 58.8 kJ ⋅ mol–1 for shallow and deep sediment horizons, respectively) was used to calculate temperature-specific decomposition rates that could be applied to environmental data. Using high-frequency water temperature data, this strategy was applied to coastal states in the conterminous United States (CONUS) where we estimated annual in situ decomposition of eroded salt marsh organic matter as 7–24% loss per year. We estimate 62.90 ± 2.81 Gg C ⋅ yr–1 is emitted from eroded salt marsh sediment decomposition in the CONUS.